For the Good of Your Health, Read This Book - Bauer, Henry (Journal of Scientific Exploration, 2020)
Essay review of The Danger Within Us: America’s Untested, Unregulated Medical Device Industry and One Man’s Battle to Survive It by Jeanne Lenzer